2018
DOI: 10.1152/ajpendo.00251.2017
|View full text |Cite
|
Sign up to set email alerts
|

Effects of periconceptional maternal alcohol intake and a postnatal high-fat diet on obesity and liver disease in male and female rat offspring

Abstract: The effects of maternal alcohol consumption around the time of conception on offspring are largely unknown and difficult to determine in a human population. This study utilized a rodent model to examine if periconceptional alcohol (PC:EtOH) consumption, alone or in combination with a postnatal high-fat diet (HFD), resulted in obesity and liver dysfunction. Sprague-Dawley rats were fed a control or an ethanol-containing [12.5% (vol/vol) EtOH] liquid diet from 4 days before mating until 4 days of gestation ( n =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
50
2

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(54 citation statements)
references
References 53 publications
2
50
2
Order By: Relevance
“…This resulted in a peak BAC of 0.03% 0.5 hour after fresh diet was first offered for the day, but by 1 hour, BAC was negligible (Probyn et al., ). The 12.5% v/v diet reported by Gårdebjer and colleagues (, ) resulted in a peak BAC of ~0.18 to 0.25% 0.5 hour after fresh diet was offered, dropping to ~0.07% at 3 hours and ~0.05% at 5 hours as reported previously (Gårdebjer et al., ). Some studies reported the concentration as percentage of EtOH‐derived calories (EDC), with most studies providing 35% EDC.…”
Section: Resultssupporting
confidence: 77%
See 2 more Smart Citations
“…This resulted in a peak BAC of 0.03% 0.5 hour after fresh diet was first offered for the day, but by 1 hour, BAC was negligible (Probyn et al., ). The 12.5% v/v diet reported by Gårdebjer and colleagues (, ) resulted in a peak BAC of ~0.18 to 0.25% 0.5 hour after fresh diet was offered, dropping to ~0.07% at 3 hours and ~0.05% at 5 hours as reported previously (Gårdebjer et al., ). Some studies reported the concentration as percentage of EtOH‐derived calories (EDC), with most studies providing 35% EDC.…”
Section: Resultssupporting
confidence: 77%
“…). Only 2 studies by Gårdebjer and colleagues (, ) treated specifically around the periconceptional period, which included exposure for 1 estrous cycle prior to mating/conception and for the first 4 days of pregnancy, prior to implantation. Ludena and colleagues () and Lopez‐Tejero and colleagues () also included a preconception exposure period of 4 weeks.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Human studies suggest that children and adolescents with FASDs have increased body fat, a higher incidence of obesity, and hypertension (18,19). However, despite additional reports using animal models suggesting that perinatal and gestational alcohol exposure are connected to poor metabolic health outcomes, there are multiple studies indicating that PAE is not associated with increased fat mass or metabolic syndrome following specific alcohol exposure windows (12,18,(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30). These conflicting reports highlight the need to clarify which adverse health outcomes are associated with PAE and to define disease mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Our result is similar to that found in a previous low-dose model in rats (Probyn et al ., 2013), as well as a study in mice with EtOH exposure restricted to late gestation (Amos-Kroohs et al ., 2018). However, other higher dose models have reported increased adiposity in PAE offspring compared to controls, particularly in males (Dobson et al ., 2012; Gardebjer et al ., 2018; Zhang et al ., 2018).…”
Section: Discussionmentioning
confidence: 99%